Reunion : a novel - Snelling, Lauraine (FaithWords, 2012)
Keira Johnson, a fifty-year-old mother of two grown sons, believes she lives a good Christian life without secrets, until she discovers a fact her late mother kept hidden all her life--a secret which shares merit with Keira's niece's unwanted pregnancy.